Terrorism, communalism and other challenges to Indian security - Gupta, Rakesh (Delhi, 2004)
This book is a product of teaching interest in the area covered. It examines conceptualisation of Indian security since independence; its evolving concerns and present threats in the context of nation-in the making. It involves the themes of renewal of the movement of sentiment to structure for renewing civic nationalism in the context of modernity. It discusses threats to political nationalism posed by chauvinism, sub-nationalism, communalism, terrorism and the games that states like USA, China and Pakistan play in destabilising the external and the internal environment. In that context Kashmir is examined. Internally it attempts a comparison between communalism and terrorism after delineating the approaches to communalism and examing the theorisation on causes and structure of terrorism. Since cinema is a popular media to disseminate dominant ideology, we examine the role of the films in raising themes of nationalism and challenges. The current scene of Hindi cinema is examined with reference to the way terrorism gets reflected in specific films. It then goes on to examine the latest shadow that the attack on the Parliament in 2001, the events in Godhra and Gujarat carnage in 2002 cast on the secular, democratic and welfarist project enshrined in the Constitution.
Keywords: Terrorism